Dampak ekspor ke Jepang dan investasi asing terhadap pendapatan perkapita masyarakat di Indonesia - Mustika, Candra; Achmad, Erni; Umiyati, Etik (Jurnal Paradigma Ekonomika, 2018)
This study aims to analyze the development of exports to Japan and foreign direct investment and per capita income in Indonesia during the period 1993-2014 also the impact of exports to Japan and foreign direct investment on per capita income of Indonesian people in that period. During research period starting in 1993-2014 where the GDP per capita has fluctuated where the average value is 15.058 in thousand rupiahs per year with an average growth of 16.61%, then the results obtained during that period the highest growth in 1998 is 50.50% and the lowest growth occurred in 2012 which was 8.46%. FDI Indonesia has fluctuated with an average value of 17,804.61 million US dollars and with an average growth of 15.35%. From the regression results on both models, the results found that in the first model the value of exports to Japan has a positive and significant effect on GDP per capita while the FDI variable does not have a positive and significant effect on GDP per capita